2005
DOI: 10.1111/j.1365-3040.2005.01362.x
|View full text |Cite
|
Sign up to set email alerts
|

Scaling ozone responses of forest trees to the ecosystem level in a changing climate

Abstract: Many uncertainties remain regarding how climate change will alter the structure and function of forest ecosystems. At the Aspen FACE experiment in northern Wisconsin, we are attempting to understand how an aspen/birch/maple forest ecosystem responds to long-term exposure to elevated carbon dioxide (CO 2 ) and ozone (O 3 ), alone and in combination, from establishment onward. We examine how O 3 affects the flow of carbon through the ecosystem from the leaf level through to the roots and into the soil microorgan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
170
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(181 citation statements)
references
References 80 publications
8
170
0
3
Order By: Relevance
“…The experiment comprises three randomized blocks containing 12, 30-m diameter FACE rings, assigned to factorial treatments of CO 2 and O 3 . Design and performance characteristics of Aspen FACE have been published and are available elsewhere (Dickson et al, 2000;Karnosky et al, 2003bKarnosky et al, , 2005Kubiske et al, 2006). Growth, O 3 , and meteorology data from a 5-year period (1999e2003) were used in this study.…”
Section: The Aspen Face Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiment comprises three randomized blocks containing 12, 30-m diameter FACE rings, assigned to factorial treatments of CO 2 and O 3 . Design and performance characteristics of Aspen FACE have been published and are available elsewhere (Dickson et al, 2000;Karnosky et al, 2003bKarnosky et al, , 2005Kubiske et al, 2006). Growth, O 3 , and meteorology data from a 5-year period (1999e2003) were used in this study.…”
Section: The Aspen Face Experimentsmentioning
confidence: 99%
“…This approach also has great potential for determining contribution of O 3 to changes measured in tree growth, and for scaling hourly effects of O 3 to cumulative impact over the growing season (McLaughlin et al, 2003). However, preliminary regression analysis of the efficacy of a modified (growing season) version of the USeCanadian O 3 air quality standard metric form by Karnosky et al (2005) has indicated that the growing season 4th highest daily maximum average O 3 concentration was potentially a good indicator of trembling aspen (Populus tremuloides Michx.) diameter growth.…”
Section: Introductionmentioning
confidence: 99%
“…These CO 2 treatments were chosen on the basis of current projections of atmospheric [CO 2 ] anticipated for 2050 (14). Detailed descriptions of the exposure systems and the CO 2 concentration dynamics are provided for DukeFACE (10), ORNL-FACE (15), AspenFACE (16,17), and POP-EUROFACE (11).…”
Section: Methodsmentioning
confidence: 99%
“…For agricultural and forest ecosystems, tropospheric ozone is considered the most widespread and damaging pollutant (Lindroth, 2010;Wittig et al, 2009). Karnosky et al (2005) reported the long-term effects of ozone pollution on several tree species, and demonstrated a negative impact throughout the whole ecosystem, not only on the trees themselves but also on associated pests and soil microorganisms.…”
Section: Introductionmentioning
confidence: 99%